The Role of ICT in Women’s Empowerment in Rural Areas of Tamilnadu with Special Reference with Kaur District - Malarkodi , k (International Journal of Psychosocial Rehabilitation, 2020)
Women affects from various discrimination, and it is thought this is heightened due to a lack of access to information. Information communication and technology (ICT) is a potential tool that can reach rural women and enrich their knowledge. This Study discusses women’s empowerment in terms of perceptual change in rural areas of Karur District after ICT intervention has been introduced. The study was undertaken in Karur district, Tamil Nadu with the sample size of 100 women who are in the rural areas. Data has been collected through questionnaire which was later evaluated using AMOS (Analysis Moment Structure) software to validate the conceptual framework. The variables taken for the study is 1. Purpose of Use & Level of Access of ICT tool,2.Gained Skills and knowledge from the ICT tool and 3.Women empowerment. The variables Purpose of Use & Level of Access and ICT Tool have positive impacts on Gained Skills and knowledge with the beta values of 0.33,0.511 respectively. Gained Skills and knowledge have positive influence on Women Empowerment (beta=0.623).